(untitled) (Quinto Sol, 2014)
The purpose of this paper is to analyze primary education policy during the administration of the self-proclaimed “Liberating Revolution”. The few studies that have examined this issue state that the Liberating Revolution government erased the traces that Peronism had left in the education system. Our interest is to review this process. To do this, we analyze the conflicts within the government, the institutional design of education governance and internal organization of schools. We ask whether despite the ideological and political ruptures, it is possible to find elements of continuity with the previous period. Our empirical observation area is the province of Buenos Aires.